Implikasi Pelanggaran Taklik Talak Terhadap Status Perkawinan Perspektif Kitab Fiqih dan UU Perkawinan - Joni Reka Jaya; Muklishin, Ahmad; Sulastri; Mufid Arsyad; Rakhmat (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2022)
Background. Taklik talak is an agreement in which the husband depends on the occurrence of a divorce for his wife if it turns out that in the future the husband violates one or all of the things in the taklik talak agreement.Aim. To find out and analyze the implications of the violation of taklik talak on marital status from the perspective of the book of fiqh and the marriage law.Methods. The type of research used is library research, namely the book of fiqh and the Marriage Law as the main sources. This research approach uses a normative approach and is analyzed qualitatively, namely based on the Marriage Law No.1 of 1974 and also studied based on fiqh books such as classical fiqh Fathul Mu'in Translation, Fathul Qarib Translation Idol Fiqh, and General References of the Ummah. The data analysis technique uses deductive techniques which are used to find out the violation of taklik talak on marital status which is then developed and described in more detail based on fiqh books and the Marriage Act.Results. Based on the study of fiqh books, the husband who violates the taklik talak he said after the marriage contract took place, then the divorce fell for his husband directly, who had already signed the taklik talak. Because it is the husband who has hung the divorce on a thing or trait, thus the divorce falls with the realization of that nature according to the words of the husband. While the violation of takalik talak on marital status according to the Marriage Act must meet the requirements in divorce, sighat taklik talak contains 2 conditions, namely alternative conditions and cumulative conditions.